KNOWLEDGE-BASED ROBOT VISION SYSTEM FOR AUTOMATED PART HANDLING - Wang, J.; Van Niekerk, T.I.; Hattingh, D.G.; Hua, T. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This paper discusses an algorithm incorporating a knowledge-based vision system into an industrial robot system for handling parts intelligently. A continuous fuzzy controller was employed to extract boundary information in a computationally efficient way. The developed algorithm for on-line part recognition using fuzzy logic is shown to be an effective solution to extract the geometric features of objects. The proposed edge vector representation method provides enough geometric information and facilitates the object geometric reconstruction for gripping planning. Furthermore, a part-handling model was created by extracting the grasp features from the geometric features. AFRIKAANSE OPSOMMING: Hierdie artikel beskryf